2020
DOI: 10.1111/ejh.13520
|View full text |Cite
|
Sign up to set email alerts
|

Anticoagulation strategies in extracorporeal circulatory devices in adult populations

Abstract: Extracorporeal circulatory devices such as hemodialysis and extracorporeal membrane oxygenation can be lifesaving; however, they are also prone to pathologic events including device failure, venous and arterial thrombosis, hemorrhage, and an accelerated risk for atherosclerotic disease due to interactions between blood components and device surfaces of varying biocompatibility. While extracorporeal devices may be used acutely for limited periods of time (eg, extracorporeal membrane oxygenation, continuous veno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 101 publications
1
33
0
Order By: Relevance
“…The consumption of platelet and thrombin may lead to consumption coagulopathy, which causes intravasular and extravascular thrombosis. Additionally, the complexity of pharmacokinetic parameters may increase due to the increase of volume distribution and random adsorption of drugs on different parts of the pump, which requires continuous dose titration of UFH ( Kato et al, 2021 ). Compared with UFH, bivalirudin has a more predictable pharmacokinetic profile, a greater reduction in thrombin, and no associated incidence of HIT ( Netley et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…The consumption of platelet and thrombin may lead to consumption coagulopathy, which causes intravasular and extravascular thrombosis. Additionally, the complexity of pharmacokinetic parameters may increase due to the increase of volume distribution and random adsorption of drugs on different parts of the pump, which requires continuous dose titration of UFH ( Kato et al, 2021 ). Compared with UFH, bivalirudin has a more predictable pharmacokinetic profile, a greater reduction in thrombin, and no associated incidence of HIT ( Netley et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, no large studies of sufficient quality are available that investigate the effects of different anticoagulation agents and targets in vvECMO. A review by Kato et al found no differences between strategies [ 167 ]. Moreover, no randomized controlled trials on anticoagulated vs. anticoagulation-free vvECMO in intracranial hemorrhage are available.…”
Section: Factors Excluded As Contraindications/additional Contraindications Onlymentioning
confidence: 99%
“…Although we adopted an anticoagulation-free operation of ECMO in an attempt to avoid bleeding risk, it would increase the risk of life-threatening thrombo-coagulopathies such as pulmonary artery thromboembolism. Therefore, other choices which have a potential to circumvent both risks concurrently would have to be considered such as intermittent operation of ECMO and use of direct thrombin inhibitors including argatroban [ 11 ].…”
Section: Discussionmentioning
confidence: 99%